A Sublatissimus Dorsi Abscess Due to Pasteurella multocida Caused by a Cat Scratch. Issue 2 (27th February 2023) - Ando, Junji; Miyata, Riyo; Harada, Masayuki; Yurugi, Satoshi; Imai, Yuichiro; Kasahara, Kei; Kuwahara, Masamitsu
Abstract : Summary: We encountered a 51-year-old male patient who was not immunocompromised. Thirteen days before his admission, his right forearm was scratched by his pet cat. Swelling, redness, and purulent discharge appeared at the site, but he did not seek medical attention. He developed a high fever and was hospitalized with a diagnosis of septic shock, respiratory failure, and cellulitis on plain computed tomography. After admission, the swelling on his forearm was relieved with empirical antibiotics, but the symptoms spread from his right axilla to his waist. We suspected necrotizing soft tissue infection and made a trial incision in the lateral chest up to the latissimus dorsi, but were unable to prove it. However, an abscess was later found under the muscle layer. Second incisions were made to allow the abscess to drain. The abscess was relatively serous, and no tissue necrosis was observed. The patient's symptoms improved rapidly. In retrospect, the patient probably already had the axillary abscess on admission. It may have been detected at this point if contrast-enhanced computed tomography had been performed, and early axillary drainage may have accelerated the patient's recovery, which could also have prevented the formation of the latissimus dorsi muscle abscess. In conclusion, the Pasteurella multocida infection on the patient's forearm induced a very unusual presentation and caused an abscess to form under the muscle, unlike necrotizing soft tissue infections. Early contrast-enhanced computed tomography may aid earlier and more appropriate diagnosis and treatment in such cases.